Variação da concentração de ozônio e efeitos genotóxicos da radiação UV no sul do Brasil - Borin, Bruna Cogo (2022)
Decreases in stratospheric ozone concentration over the last 40 years influenced by the Antarctic ozone hole have altered the incidence levels of solar ultraviolet (UV) radiation in the south of the Southern Hemisphere. Exposure of organisms to UV radiation leads to the formation of different types of DNA lesions. We investigated the genotoxic potential of incident solar UV radiation in the region of Santa Maria, RS, through the quantification of lesions formed in DNA samples exposed to the sun through the use of the DNA Dosimeter System, on different days of the four seasons, in order to correlate it with the local UV radiation incidence data collected by specific radiometers. We analyzed two databases comprising 17 years of daily measurements of solar UVB and UVA radiation and 43 years of daily measurements of stratospheric ozone concentration in this region. Surprisingly, we observed that doses of solar UV radiation as high as those observed in summer could be monitored in spring, consequently matching the rates of DNA lesion formation between these seasons. The incidence of solar UVB radiation has been increasing over the last fifteen years and this increase is more pronounced in the warmer seasons (spring and summer). By investigating the possible causes of this phenomenon of increased UVB radiation and the high genotoxic potential of sunlight, we found a general trend of stratospheric ozone depletion in South America for all seasons between 1979 and 2021. Our results indicate that the South America continent is undergoing an unprecedented process of changes in relation to the stratospheric ozone concentration, as well as the increase in terrestrial UVB radiation doses and its genotoxic effects. The results and conclusions obtained in this study may be very useful to guide the population, especially those residing in the central region of RS, about the dangers of excessive sun exposure, as well as to expand studies focused on the causes of variations in ozone concentration throughout the southern hemisphere.